The comparative study on - in which sector the financial institutions are more interested to provide business loans in Bangladesh , reasons of loan default and Risk mitigating process of credit risk management of IDLC Finance Limited. - Hossain, Md. Shakhawat (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.